Drug use in pregnancy and labor - Risanto Siswosudarmo Risanto Siswosudarmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
Drug use in pregnancy should consider two main things, the first is its indication to the mother and the second, the more important, is its potential side-effect to the fetus. The aim of this paper is to review the possibility of side-effects of drugs commonly used during pregnancy, labor and delivery.Side-effects of drugs to the fetus are classified into three catagories namely1. embryotoxic effect,2. teratogenic effect and 3. minor side-effect.Embryotoxic effect is the most severe side-effect causing CO the death of the conceptus which usually terminates in early abortion. Teratogenic effect is an effect that causes major congenital anomalies. This effect happens if certain drugs are taken during the phase of organogenesis, i. e. between the third and the eighth week after conception. The minor side-effect may occur if some potential drugs are taken during the fetal period, i. e. during the phase of cellular hypertrophia or after the second month of pregnancy.Based on the teratogenic property of drugs, they can be classified into three major divisions:1. known teratogens such as thalidomide, anticancer drugs, certain hormones, sodium valproate and isotretionine,2. probable teratogens such as anticonvulsant, tobacco, alcohol, lithium, warfarin, and3. possible teratogens such as barbiturate, sulphonamide, certain an timalarials, oral an ndiabetics, LSD, certain antibiotics and some vaccines.The severity of anomalies in the fetus depends on the type of drugs, dosage, phase of fetal development, and species sensitivity. The general rule is all potential teratogenic drugs should be avoided during pregnancy, especially during the first trimester. Drugswith certain teratogenic effect should absolutely not be used during pregnancy, in spite of its indication.Key Words: drugs - pregnancy - teratogens - embryo toxic effects - congenital malformation